Vibration analysis of piping connected with shipboard equipment - Tripathi, Radharaman; Jadhav, Tushar A.; Gaikwad, Mahesh K.; Naidu, Mithul J.; Gawand, Aishwarya B.; Kaya, Duran; Salunkhe, Sachin; Cep, Robert; Abouel Nasr, Emad (Frontiers in Mechanical Engineering, 2024)
The piping system connected with the shipboard equipment may be subjected to excessive vibration due to harmonic base excitation produced by hydrodynamic force imposed on the propeller blades interacting with the hull and by other sources. Vibration design aspects for shipboard pipework are often ignored, which may cause catastrophic fatigue failures and, consequently, leakage and spillage in the sea environment. Without dedicated design codes, the integrity of shipboard equipment against this environment loading can be ensured by testing as per test standard MIL-STD-167-1A (2005). However, in many cases, testing is not feasible and economically viable. Hence, this study develops an FE-based vibration analysis methodology based on MIL-STD-167-1A, which can be a valuable tool to optimize the testing requirement without compromising the integrity of these piping systems.